Cas1 and Cas2 From the Type II-C CRISPR-Cas System of Riemerella anatipestifer Are Required for Spacer Acquisition - He, Yang; Wang, Mingshu; Liu, Mafeng; Huang, Li; Liu, Chaoyue; Zhang, Xin; Yi, Haibo; Cheng, Anchun; Zhu, Dekang; Yang, Qiao; Wu, Ying; Zhao, Xinxin; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) proteins provide acquired genetic immunity against the entry of mobile genetic elements (MGEs). The immune defense provided by various subtypes of the CRISPR-Cas system has been confirmed and is closely associated with the formation of immunological memory in CRISPR arrays, called CRISPR adaptation or spacer acquisition. However, whether type II-C CRISPR-Cas systems are also involved in spacer acquisition remains largely unknown. This study explores and provides some definitive evidence regarding spacer acquisition of the type II-C CRISPR-Cas system from Riemerella anatipestifer (RA) CH-2 (RA-CH-2). Firstly, introducing an exogenous plasmid into RA-CH-2 triggered spacer acquisition of RA CRISPR-Cas system, and the acquisition of new spacers led to plasmid instability in RA-CH-2. Furthermore, deletion of cas1 or cas2 of RA-CH-2 abrogated spacer acquisition and subsequently stabilized the exogenous plasmid, suggesting that both Cas1 and Cas2 are required for spacer acquisition of RA-CH-2 CRISPR-Cas system, consistent with the reported role of Cas1 and Cas2 in type I-E and II-A systems. Finally, assays for studying Cas1 nuclease activity and the interaction of Cas1 with Cas2 contributed to a better understanding of the adaptation mechanism of RA CRISPR-Cas system. This is the first experimental identification of the naïve adaptation of type II-C CRISPR-Cas system.